Antibiotic Resistance and Biofilm Formation in Pseudomonas aeruginosa from Different Clinical Samples in Nasiriya, Iraq - Saud, Ali; Raghad Hassan Hussein; Yousor Majid Jameel (University of Thi-Qar Journal of Science, 2025)
Background: Pseudomonas aeruginosa is recognized as the main cause of nosocomial infections. The study aimed to investigate biofilm formation and antibiotic resistance patterns in clinical isolates of P. aeruginosa from various clinical samples from 12 to 70 ages. Methodology: This study included 120 samples obtained from Al-Hussein Teaching Hospital, Al-Nasiriya Teaching Hospital, Al-Haboubi Teaching Hospital, and Mohammed Al-Mousawi Children’s Hospital in Nasiriya from January 2023 to June 2023. The samples included 56 wound swabs from cancer patients, 27 burn swabs from burn patients, 18 sputa, 14 ear swabs, and 5 bronchial-aspirate samples. The ages of the patients ranged between 12 and 70 years, and both sexes were represented. The drug susceptibility pattern and biofilm formation were performed for all the isolates. Results: After the final diagnosis, 80 samples (67%) were confirmed to be Pseudomonas aeruginosa. These isolates were obtained from 61 males (76.25%) and 19 females (23.75%).e highest resistance of P. aeruginosa to antibiotics was against the antibiotics Cefepime (96.25%), Amikacin (91.25%), Gentamicin (81.25%), and resistance to Ciprofloxacin was (76.25%), Ceftazidime (66.25%), Piperacillin (48.8%), and Aztreonam (47.5%). On the other hand, the lowest resistance reported in the present study was towards Colistin Sulphate (1.25%), followed by Imipenem (3.75%) and Meropenem (5%). In addition, the results of biofilm formation showed that 57 (71.25%) were non-biofilm producers, 10 (12.5%) were weak biofilm producers, 11 (13.75%) were moderate biofilm producers, and 2 (2.5%) were strong biofilm producers. Conclusion: no correlation was found between antibiotic resistance and biofilm formation.